Treatment utilization and barriers to treatment: Results of a survey of dependent methamphetamine users - Lee Nicole K; Harney Angela; Kenny Pauline; Pennay Amy (BMC, 2011)
Abstract Background Australia has one of the highest rates of methamphetamine use in the world; however, treatment access for methamphetamine is comparatively low. This descriptive study aimed to identify patterns of treatment utilization and perceived barriers to accessing treatment among dependent methamphetamine users in the hope that such information will enable services to more appropriately respond to this group. Methods One hundred and twenty-six methamphetamine users who had a current or past history of methamphetamine dependence were interviewed about their experiences of, and perceived barriers to, treatment. Results Treatment utilization among methamphetamine users was reportedly low. One of the main reasons cited for not accessing treatment was that methamphetamine users did not perceive their drug use to be a problem (despite apparent levels of dependence). Self-detoxification with the use of other licit and illicit drugs was high among this group. Participants identified a lack of confidence in the ability of treatment services to address methamphetamine dependence and the 'opiate-centric' nature of treatment services as significant blocks to treatment entry. Suggestions for improvement by participants included operating specialist services for methamphetamine users, placing an emphasis on responsiveness and routinely involving case management services for this group. Discussion and Conclusions To improve service delivery, treatment services should reorient their services to better address the needs of methamphetamine users by making small changes such as specific opening times for methamphetamine users or using a dedicated space for methamphetamine treatment. Alternative options such as online treatments and specialist methamphetamine clinics should be considered for methamphetamine users.